Storage stability of low-fat chicken sausages - Andres, Silvina Cecilia (2006)
Storage stability of low-fat chicken sausages formulated with fresh breast chicken meat with 0%, 2%, and 5% of added beef tallow was examined during 50-day refrigerated storage. The formulations also contained whey protein, guar and xanthan gums, NaCl, NaNO2, ascorbic acid and sodium tripolyphosphate. Samples were heat-processed until a final internal temperature of 74 °C was reached, cooled, vacuum packaged and stored at 4 °C. Formulations showed good thermal stability, with process yields ranging between 94% and 97%, and purge losses less than 9.7% at the end of the study. Water activity slightly decreased during the first 28 days of storage and remained constant afterwards for all the tested samples, while pH and color parameters remained constant. As fat content increased a harder, more gummy and cohesive product was obtained, with higher chewiness and lower springiness and resilience values. Neither coliforms nor sulfite-reducing Clostridium were detected during the storage of the samples. Psychrotrophic lactic acid bacteria was the dominant microflora reaching levels lower than 7 log CFU/g after 50 days of storage at 4 °C. Formulated low-fat chicken sausages had acceptable sensory scores independently of the added fat. Extra lean products with very good stability and quality attributes were obtained.